2012
DOI: 10.1371/journal.ppat.1002935
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Infection Links Epithelial and B Cell Tropisms of Murid Herpesvirus-4

Abstract: Gamma-herpesviruses persist in lymphocytes and cause disease by driving their proliferation. Lymphocyte infection is therefore a key pathogenetic event. Murid Herpesvirus-4 (MuHV-4) is a rhadinovirus that like the related Kaposi's Sarcoma-associated Herpesvirus persists in B cells in vivo yet infects them poorly in vitro. Here we used MuHV-4 to understand how virion tropism sets the path to lymphocyte colonization. Virions that were highly infectious in vivo showed a severe post-binding block to B cell infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 68 publications
3
98
0
Order By: Relevance
“…We therefore concluded that the increasing contribution to virus productivity by B cells is a general feature of MHV-68 infection and is independent from the infection route. It was recently shown that the efficiency of B cell infection in vitro was improved when MHV-68 was produced by myeloid cells, while virus produced by epithelial cells or fibroblasts poorly infected B cells (60). Our results suggest that virus produced by EC also infect B cells efficiently.…”
Section: Discussionsupporting
confidence: 50%
“…We therefore concluded that the increasing contribution to virus productivity by B cells is a general feature of MHV-68 infection and is independent from the infection route. It was recently shown that the efficiency of B cell infection in vitro was improved when MHV-68 was produced by myeloid cells, while virus produced by epithelial cells or fibroblasts poorly infected B cells (60). Our results suggest that virus produced by EC also infect B cells efficiently.…”
Section: Discussionsupporting
confidence: 50%
“…However, the immune system already efficiently channels foreign antigens to myeloid cells. MuHV-4 efficiently targets dendritic cells and macrophages without an obvious need for further recruitment (31,44), and the MCMV MCK2 made little obvious contribution to myeloid cell recruitment into lungs: its disruption reduced Gr-1 ϩ cell numbers only transiently in BALB/c mice and had no significant effect in C57BL/6 mice, nor was the level of viremia during the acute phase of infection reduced. Thus, the salivary infection defect of MCK2 Ϫ MCMV may reflect that MCK2 functions after dissemination (18); for example, its chemokine function could have more of an impact in less inflammatory settings.…”
Section: Discussionmentioning
confidence: 99%
“…MCMV strain K181 with a premature stop codon in m131 (18) and other gL-positive (gL ϩ ) MCMVs were propagated on NIH 3T3 cells. eGFP-expressing murid herpesvirus 4 (MuHV-4) (30), floxed color-switching MuHV-4 (MHV-RG) (31), and herpes simplex virus 1 (HSV-1) (32) were grown in BHK-21 cells. Infected cell cultures were cleared of cell debris by low-speed centrifugation (500 ϫ g, 10 min).…”
Section: Glmentioning
confidence: 99%
“…inoculation, it reaches B cells first in the superficial cervical lymph nodes (SCLN). It reaches the NALT only via systemic dissemination (18).…”
mentioning
confidence: 99%